2005
DOI: 10.1002/eat.20085
|View full text |Cite
|
Sign up to set email alerts
|

The dearth of psychological treatment studies for anorexia nervosa

Abstract: The review highlights the effectiveness of one particular treatment modality for adolescents, but emphasizes the compelling need for further and larger systematic investigation into treatments for both adolescent and adult AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 49 publications
2
53
1
6
Order By: Relevance
“…In the present review 9 RCTs were found, a number higher than that found in a systematic review conducted for AN treatment in childhood and adolescence, published in 2005, which found only five studies with this design 11 . Although the RCT design is considered to be the gold standard for evaluating the efficacy of treatments, among the studies analyzed, several methodological limitations have decreased the quality of the scientific evidence produced.…”
Section: Designcontrasting
confidence: 60%
See 3 more Smart Citations
“…In the present review 9 RCTs were found, a number higher than that found in a systematic review conducted for AN treatment in childhood and adolescence, published in 2005, which found only five studies with this design 11 . Although the RCT design is considered to be the gold standard for evaluating the efficacy of treatments, among the studies analyzed, several methodological limitations have decreased the quality of the scientific evidence produced.…”
Section: Designcontrasting
confidence: 60%
“…However, given the limited number of studies and various methodological limitations found, it is not possible to make a conclusion on the efficacy of the interventions. This aspect, as already identified in a previous review 11 , remains stable and constitutes an important limitation in the field of ED in childhood and adolescence.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…These considerations, however, do not negate the need for effectiveness research (Milne & Paxton, 1998), particularly with adult inpatient populations where the few existing studies show how poorly adult anorexics fare in treatment compared with their adolescent counterparts (Le Grange & Lock, 2005). Recent increases in mid-life eating disorder cases have also spurred interest in the characteristics and needs of older patients with AN (Cumella & Rally, 2008).…”
Section: Introductionmentioning
confidence: 96%